Evaluation of two sorghum (Sorghum bicolor (L.)Moench) stover varieties as sole roughage source for dairy cattle - and RM Sundaram, S B N Rao et al. (Indian Journal of Dairy Science, 2025)
The present experiment was conducted to evaluate two popular sorghum stover varieties grown in parts of Karnataka and Maharashtra. The varieties are M35-1 (very old popular rabi jowar released for dry regions of Maharashtra) and PVK-1009 (Kharif Sorghum released for Maharashtra having more minerals). They have been subjected for chemical composition and in vitro studies using standard procedures. M35-1 has significantly higher CP (P<0.05) and Zn (P<0.01) than PVK-1009. ADF and cellulose were more (P<0.05) in PVK-1009 than M35-1. TA, NDF and HC were significantly higher (P<0.01) in PVK-1009. In vitro results were non-significant (P> 0.05) except ME (P<0.05) which is greater in M35-1 variety. On the basis of present findings it is concluded that Rabi jowar variety M35-1 is nutritionally superior in CP, Zn and ME. However, Fiber fractions were higher in PVK-1009 and digestibility parameters (IVDMD, IVOMD) were comparable. Metabolizable energy (ME MJ/kg) was higher in M35-1 due to higher CP content. It can be concluded that both sorghum varieties (M35-1 and PVK-1009) were suitable for feeding livestock both Kharif and Rabi seasons.